Winter night at Liffey : a collection of solo piano pieces - Crump, Stephen James; Brown, Bob, 1944- ([Tasmania] : Bob Brown and Steve Crump, 2018)
"These piano pieces offer musical sketches inspired by four poems written by Dr Bob Brown, as published in "In Balfour Street" (New Print, 2010). Bob's poems are vivid, rugged, gentle, funny, brave accounts of various events in his life in the 1970s. The four musical sketches were improvised by conjuring up what the poems meant to me, focussing on key events in each: the peacefulness of the snow at the end of a night time storm at Liffey under the Western Tiers in Tasmania..."--Foreword by the composer.
Winter night at Liffey -- Katie Kingston -- In Balfour Street -- Wynyard Girl.
Title from cover.
staff notation.
Keywords: Brown, Bob, -- 1944- -- Poetry; Crump, Stephen James -- Scores; Piano music -- Scores; Australian poetry -- Tasmania -- 20th century; Australian poetry -- Tasmania -- 21st century; Australian poetry -- Musical settings; Poetry readings (Sound recordings); Tasmania -- Songs and music; Tasmania -- Poetry; Scores